Looking for William - Jennifer Ruiz-Morgan (The Grove, 2022)
Literary tourism has recently emerged as a lively field of research, especially in nineteenth-century studies. As a cultural phenomenon it has proved to be particularly popular in the British Isles, where its origins can be traced back to the eighteenth century. This essay analyses literary tourism in relation to one of England’s most renowned authors: Shakespeare. Garrick’s 1769 Jubilee is explored to explain how this well-orchestrated commemorative event paved the way for the earliest pilgrimages to Stratford-upon-Avon. Secondly, the Shakespeare family homes, especially the Birthplace, are analysed as historical national icons that have elicited ideas of Englishness. Finally, there is a discussion on authenticity in relation to the Birthplace and The Globe. Using theoretical terminology coined by Lacan and Baudrillard, the essay seeks to demonstrate the inability to fully experience authenticity, as it is impossible to access a reality—Shakespeare’s past—that has ceased to exist.